Strategi Pembelajaran Mandiri Siswa dalam Meningkatkan Kemahiran Menulis Bahasa Arab di MA Islamic Centre Al-Hidayah Kampar - Ramadhaniati Fitri; Dwi Binti Masfufah; Nur Azizah; Promadi (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2026)
Writing skill remains one of the four difficult and complex language skills in Arabic that students must master, and it continues to receive increasing attention in academic discussions. Mastering Arabic writing requires additional effort; therefore, students need to make consistent efforts to improve their writing skills. Among the efforts students can undertake is continuous writing practice, such as writing sentences according to the number of nouns and verbs. The main problem addressed by this study concerns how students make efforts to improve their writing skills both inside and outside the classroom, as well as the factors that influence these efforts at Islamic Boarding School Al-Hidayah in Kampar. This study employs a qualitative research method with a descriptive analysis approach. Data were collected through interviews with students of Islamic Boarding School Al-Hidayah in Kampar who reside in the school dormitory. The results indicate that students’ efforts to improve their writing skills during classroom learning include studying grammar, practicing writing consistently, and regularly consulting dictionaries to acquire new vocabulary. Meanwhile, their activities outside the classroom include writing assignments, keeping personal diaries in Arabic, and publishing memorized expressions on blogs. The factors that influence students’ efforts to improve their writing skills are predominantly internal factors, such as motivation, intention, interest, concentration, intelligence, satisfaction, and experience.